Study of the influence of breed and grinding modes on the specific productivity of grinding skin - Gayda, S.V.; Petryshak, I.V.; Somar, G.V. (Forestry, Forest, Paper and Woodworking Industry, 2020)
It is investigated that wood species influences the indicators of grinding process: surface roughness, specific skin productivity, skin efficiency, cutting force, which in general also depend on the speed of cutting and feeding, pressing force, abrasive grain size. It is confirmed that the specific productivity of the skin during the grinding of spruce is higher by 14.25-18.77% than when processing oak wood. It is established that with the increase of the feed rate the height of the irregularities increases, as the thickness of the chips, which is removed by one active grain, increases. This is significant for tree species with lower density and hardness. It is investigated that with the increase of the feed rate during the treatment of the oak wood surface the specific productivity of the sanding skin increases by 24.62-31.40%, and in spruce – by 23.14-24.02%. It is established that with the increase of grinding time during the treatment of the oak wood surface the specific productivity of the skin decreases by 162.68-190.40%. and in spruce – by 114.29-176.09%. The specific productivity of the skin during the grinding of spruce is higher by 18.90-22.47% than when processing oak wood. It is confirmed that with increasing grain size of the abrasive, the purity of the polished surface deteriorates, ie the value of the roughness of the treated surface is directly proportional to the grain size of the abrasive. It was found that the presence of oils in spruce causes rapid salinization of the skin, ie to reduce its efficiency. It was found that the sequence of use of the positions of the skins help to increase the productivity of grinding and obtain the purity of the desired class. To carry out effective grinding to obtain a quality surface, the following input processing values are recommended: cutting speed 20-30 m / s; feed speed 6-8 m / min; specific clamping force 2.2-4.4 kPa; grain size of skins: P180-P150; P120-P100; P90-P60.